The social-class gap in negotiation: Lower-class individuals negotiate less and face more backlash - Ying Lin; Jackson G. Lu; Michele J. Gelfand (Proceedings of the National Academy of Sciences, 2026)
Economic inequality has widened considerably in the United States and globally, raising pressing questions about the mechanisms that reproduce social stratification. One prominent manifestation of this inequality is the “class ceiling” in organizations: individuals from lower social classes earn less and advance more slowly than their higher-class counterparts, even with comparable credentials. We identify a crucial behavioral pathway contributing to this class ceiling: a social-class gap in the propensity to negotiate. We propose that lower-class individuals are less likely to initiate negotiations than their higher-class counterparts, a pattern that can compound economic disadvantage over time. Across four studies (total N = 10,211)—including a nationally representative sample of employees (Study 1), a sample of business school students (Study 2), a field study of an online labor market (Study 3), and a survey study of workplace negotiations and career outcomes (Study 4)—we find consistent evidence for this gap. This gap is partially explained by lower-class individuals’ reduced sense of power and heightened concerns about social backlash. Additionally, Study 5 ( N = 1,133) finds that such concerns may be justified: an experiment with human resources (HR) professionals shows that identical negotiation requests elicit stronger social backlash when initiated by lower-class (vs. higher-class) individuals. Together, these findings reveal a pernicious double bind for lower-class individuals: remaining silent perpetuates economic disadvantage, yet initiating negotiation exposes them to greater social penalties. Addressing this double bind is critical for ensuring that negotiation serves as a vehicle for upward mobility rather than a gatekeeper of privilege.